Metaphors in Learner English - Nacey, Susan (Metaphor in language, cognition, and communication,, 2013)
This volume presents results from a corpus-based investigation into the metaphorical production of foreign language learners, comparing texts written by Norwegian (L2) learners of English with those written by British (L1) students. Three types of questions are addressed. The first has empirically measured answers: For example, do L2 English writers produce more metaphors than L1 novice writers? How frequent are novel metaphors in an L2, as compared with an L1? The second type has more subjective answers: How creatively do L2 English learners employ metaphor? Are they even expected to be able.